Proposal of a stable B3S nanosheet as an efficient hydrogen evolution catalyst - Wu, Hong; Li, Xingxing; Zhang, Ruiqi; Yang, Jinlong (Journal of materials chemistry. A, Materials for energy and sustainability, 2019)
Exploring noble metal-free catalysts that have high stability, good electrical conductivity and intrinsic catalytic sites with activity comparable to Pt is very desirable for the hydrogen evolution reaction (HER). Using a global minimum structure search combined with first-principles calculations, we propose a two-dimensional (2D) boron sulfide material as a catalyst: the B3S nanosheet. Ab initio molecular dynamics simulation confirms its stability up to 1300 K. With a metallic band structure and delocalized Fermi electronic states, the B3S nanosheet is expected to be highly conductive. By investigating the hydrogen adsorption Gibbs free energy, which is the activity descriptor of the HER, the B–B bridge sites of the B3S nanosheet are identified as active sites with activity close to that of Pt and tunable by controlling the hydrogen coverage or applying an external strain. These results imply that the designed B3S nanosheet has great potential to be a low-cost and high-efficiency catalyst for the HER.